IMPLEMENTATION OF THE DEVELOPMENT PROGRAM THAT JUST AS THE PRO-POOR GOVERNMENT POLICIES - Sri Suatmiati (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2017)
In Several states, social security for citizens is place to protect marginalized groups in order to maintain access to public services are rudimentary, such as services to meet the needs from the perspective of political economy known as basic need. Public welfare provision in the state system includes services in the areas of basic education, health and housing are cheap and good quality, if Necessary, free as in Western Europe is a cluster of countries are quite intense in terms of the welfare state principles. Free education and health is a major concern in Western Europe to get subsidies. The Data agency (BPS) said that the Indonesian population in 2010 income Rp.27,0 million a year. There are poor people Whose population is 80 percent of the population only contributes about 20 percent of GDP. There are the wealthy once or people who enter the category earn more than 30,000 dollars a year, but there are Also people with disabilities living income or 2 dollars per day (730 dollars a year), the which are still 100 million people. It means there is a huge gap. The words fair, equitable, wellbeing and prosperity was growing dimmer and the faint sound. This condition shows how there is no equity in income Because there is no strong will to realize the vision for the welfare of society. Impossible Anti-poverty program run properly if the governance of the state and society is not yet fully base on the welfare state system. Anti-poverty programs intertwine with the application of individual taxation that is progressive. If taxation without concept, poverty reduction strategy with the government has not gone According to the terms of the welfare state that is pro-poor.